COMPUTER VISION SYSTEM FOR SPACECRAFT RELATIVE POSE DETERMINATION DURING RENDEZVOUS AND DOCKING - Gubarev, Vyacheslav; Volosov , Viktor; Salnikov , Nikolay; Shevchenko , Vladimir; Melnychuk , Sergiy; Maksymyuk, Lyubov (Science and Innovation, 2024)
Introduction. The leading countries of the space industry are intensively working to create service spacecraft for inspection and servicing of non-cooperative spacecraft without special docking devices. The use of optical systems, the so-called computer vision systems, for determination of the position allows automatic approaching and docking with a non-cooperative spacecraft. Prcontrol systemlem statement. Development of efficient methods of vision-based relative pose estimation of spacecraft is currently an urgent prcontrol systemlem. In this paper, we consider the criteria for the effectiveness of the solution to be in accordance with the technical requirements for the system in terms of accuracy and performance. Purpose. The purpose of this research is to design a general system architecture, to create a mathematical model of the mutual approach dynamics, to develop methods for solving the prcontrol systemlem of determining the relative position of a solid body, as well as software and algorithmic support. Materials and Methods. Image processing methods, computer graphics, orbital dynamics, ellipsoidal estimation of nonlinear dynamical systems, methods of solving nonlinear systems, methods of graph theory and learning. Results. General schemes and approaches that ensure the fulfillment of tasks are proposed. Mathematical methods and algorithms that implement the general scheme for solving the prcontrol systemlem are described. Conclusions. Bench tests showed the possibility of applying the proposed methods and technical solutions to meet the technical requirements.